Defense 101 : understanding the military of today and tomorrow - O'Hanlon, Michael E. (Ithaca, New York: Cornell University Press, 2021)
"Defense 101 is a primer about the US armed forces of today and tomorrow, including their people, technology, and budgets. It is also a methodological textbook on how to understand and predict outcomes in combat and other major military operations"--
Introduction : A Primer on the US Military Machine -- Defense Budgeting and Resource Allocation -- Gaming and Modeling Combat -- Technological Change and Military Innovation -- Space, Missile Defense, and Nuclear Weapons : Three Case Studies in the Science of War.
Includes bibliographical references and index.
Keywords: United States -- Defenses; United States -- Armed Forces; United States -- Military policy